Lawsonia intracellularis: Revisiting the Disease Ecology and Control of This Fastidious Pathogen in Pigs - Karuppannan, Anbu K.; Opriessnig, Tanja (Frontiers in Veterinary Science, 2018)
Lawsonia intracellularis is an anaerobic obligate intracellular bacterium infecting the small intestine and infrequently also the large intestine of pigs and other animals including hamsters and horses. The infection is characterized by proliferation, hemorrhage, necrosis, or any combination commonly referred to as “ileitis”; affecting the health and production efficacy of farmed pigs. Despite decades of research on this pathogen, the pathogenesis and virulence factors of this organism are not clearly known. In pigs, prophylaxis against the infection is achieved by either administration of subtherapeutic levels of in-feed antibiotic growth promoters or vaccination. While the former approach is considered to be effective in L. intracellularis control, potential regulations on subtherapeutic antibiotics in many countries in the near future may necessitate alternative approaches. The potential of manipulating the gut microbiome of pigs with feed ingredients or supplements to control L. intracellularis disease burden is promising based on the current understanding of the porcine gut microbiome in general, as well as preliminary insights into the disease ecology of L. intracellularis infection accrued over the last 30 years.